The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/jvi.01039-13
|View full text |Cite
|
Sign up to set email alerts
|

Differing Epidemiological Dynamics of Influenza B Virus Lineages in Guangzhou, Southern China, 2009-2010

Abstract: The epidemiological and evolutionary dynamics of the two cocirculating lineages of influenza B virus, Victoria and Yamagata, are poorly understood, especially in tropical or subtropical areas of Southeast Asia. We performed a phylogenetic analysis of the hemagglutinin (HA) and neuraminidase (NA) sequences of influenza B viruses isolated in Guangzhou, a southern Chinese city, during 2009 to 2010 and compared the demographic and clinical features of infected patients. We identified multiple viral introductions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
54
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 45 publications
12
54
2
Order By: Relevance
“…Our phylogenetic results showed that the influenza B virus strains circulating in Beijing during the 2013-2014 influenza season were dominated by reassortants with the Yamagata lineage of hemagglutinin and the Victoria lineage of neuraminidase. This new finding is clearly different from those of previous studies [4,32,33]. McCullers et al [23] demonstrated that influenza B viruses adopt reassortment as a means to acquire genetic variability, and that this strategy has shaped the natural evolution of influenza B viruses.…”
Section: Discussioncontrasting
confidence: 69%
“…Our phylogenetic results showed that the influenza B virus strains circulating in Beijing during the 2013-2014 influenza season were dominated by reassortants with the Yamagata lineage of hemagglutinin and the Victoria lineage of neuraminidase. This new finding is clearly different from those of previous studies [4,32,33]. McCullers et al [23] demonstrated that influenza B viruses adopt reassortment as a means to acquire genetic variability, and that this strategy has shaped the natural evolution of influenza B viruses.…”
Section: Discussioncontrasting
confidence: 69%
“…Evidence suggests differences in the age distribution of patients infected with the B/Yamagata or B/Victoria lineages, with the latter appearing to be more frequently identified in younger age groups . Although the lineage seems to have generally no impact on the clinical outcome of the infection, recent data from Hong Kong suggested that B/Victoria viruses may be associated with more influenza B hospitalization in children compared with B/Yamagata viruses .…”
Section: Discussionmentioning
confidence: 99%
“…Some amino acid features within the HA and NA of these 2 viruses were the same as those in the A/Shanghai/2/2013(H7N9) strain: L226 and G228 in HA, believed to control host receptor specificity; the cleavage site in HA, relevant for virulence; a deletion in NA stalk (position 69–73), associated with the adaption to gallinaceous hosts; and R294 in NA, related to virus sensitivity to oseltamivir ( 5 ). The HA and NA sequences of A/Hangzhou/10–2/2014(H1N1)pdm09 and B/Hangzhou/17–2/2014 were very close to those of A(H1N1)pdm09 virus and B/Yamagata-lineage viruses that had recently circulated in China ( 6 , 7 ). …”
mentioning
confidence: 88%